Delivering inspiring doctoral assessment - Denicolo, Pam; Duke, Dawn; Reeves, Julie, 1963- (London : SAGE Publications Ltd, 2020)
This book provides academics, trainers and supervisors worldwide the tools to effectively support doctoral students in the assessment process. Its multidisciplinary approach makes it a uniquely useful manual for the examination of works from conception to completion, and dissemination – in both formative and summative assessments. It gives clear guidance on: • How assessment is structured and conducted, • Activities and questions for the supervision of vivas and public debates, • How to manage assessment outcomes. This book equips early career assessors to effectively perform their duties and supportive roles, and is a valuable resource for doctoral students seeking insight into the rationale behind the ways in which their preparation is structured and delivered.
Includes index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Doctoral students -- Supervision of